The prokaryotic activity of the IGR IRESs is mediated by ribosomal protein S1. Issue 16 (30th August 2022) - Roberts, Luc; Wieden, Hans-Joachim
Abstract: Internal ribosome entry sites (IRESs) are RNA elements capable of initiating translation on an internal portion of a messenger RNA. The intergenic region (IGR) IRES of the Dicistroviridae virus family folds into a triple pseudoknot tertiary structure, allowing it to recruit the ribosome and initiate translation in a structure dependent manner. This IRES has also been reported to drive translation in Escherichia coli and to date is the only described translation initiation signal that functions across domains of life. Here we show that unlike in the eukaryotic context the tertiary structure of the IGR IRES is not required for prokaryotic ribosome recruitment. In E. coli IGR IRES translation efficiency is dependent on ribosomal protein S1 in conjunction with an AG-rich Shine-Dalgarno-like element, supporting a model where the translational activity of the IGR IRESs is due to S1-mediated canonical prokaryotic translation.